A Survey on High School Students’ Preferences toward the Use of Social Media as Online Learning Tools - Jaya, Hariswan Putera; Dari, Tita Ratna Wulan; Zuraida, Zuraida; Wijaya, Alhenri (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Along with the rapid development of technology, various kinds of social media applications are emerging and offering their users a variety of benefits. Social media such as WhatsApp, Instagram, YouTube, Telegram, and Google Classroom, to name but a few, are the ones that are often used by students for online learning because they can be used easily, anywhere and anytime. This study aimed at finding out whether or not the students used social media for learning, the kinds of social media mostly preferred by the students, and the reasons for their preferences.Â The population of this study was 625 students from two state senior high schools in Palembang. For the sampling technique, this study applied the probability-sampling technique. Then, to meet the standard number of samples in a survey study, the writers took 14% of the population. It meant there were 88 research samples, specifically 44 students from each school. To collect the data, the questionnaire and interview were used in this research. As the results, all participants showed that they have greatly exposed themselves to social media during the